Optimization Research of Energy Structure in Hebei Province - Jinying Li; Zhifen Xu; Chunlian Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the case of excessive energy consumption and energy consumption structure is irrational in Hebei Province, energy structure optimization has become increasingly important. This paper establishes a multi-objective decision model of energy structure optimization through regression analysis by collecting large amounts of data of energy consumption and energy-related investments and pollution control over the years, through a comprehensive and systematic analysis of the model, then using genetic algorithms to solve the model ,the result verifies the validity of the method .Finally,the paper analyzes the result and clarifies the future direction of development of the energy structure in Hebei Province. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.3846